E-GOVERNMENT AS A TOOL FOR COMBATING CORRUPTION IN UKRAINE: ANALYSIS OF GLOBAL EXPERIENCE AND NATIONAL BARRIERS (Coordinates of Public Administration, 2026)
The article reveals the role of e-government as a key tool for increasing the transparency and effectiveness of Ukraine's anti-corruption policy under martial law. It is proven that the development of digital services, open registers, automated procedures and risk-based analytics tools forms a new model of accountable digital governance, which minimizes the discretionary influence of officials and ensures the controllability of management decisions. Based on the analysis of international research, global trends in digital transformation are outlined and it is confirmed that a high level of digital maturity of states correlates with a decrease in corruption risks and an increase in public trust. An assessment of Ukraine's positions is carried out and the dynamic progress of digital statehood after 2018 is determined, despite the existing infrastructure, institutional and security restrictions. The main challenges of implementing digital anti-corruption policy in Ukraine are systematized — regulatory fragmentation, insufficient integration of state registers, uneven digital infrastructure, cyber risks and low digital culture. Strategic directions for overcoming them are proposed, in particular, the unification of electronic legislation, automation of inspections, deepening of algorithmic control, development of AI-screening, strengthening of cyber defense and expansion of digital literacy programs. The results of the study identify e-governance as a system-forming element of anti-corruption reform and create the basis for the formation of an effective model of digital integrity in the war and post-war period.